Demographic characteristics and complications of open and minimal invasive surgeries for renal cell carcinoma: a population-based case–control study in Taiwan - Chang YH; Chang SW; Liu CY; Lin PH; Yu KJ; Pang ST; Chuang CK; Kan HC; Shao IH (Dove Medical Press, 2018)
Ying-Hsu Chang,1,2,* Su-Wei Chang,3,4,* Chung-Yi Liu,1,2 Po-Hung Lin,1,2 Kai-Jie Yu,1,2 See-Tong Pang,1,2 Cheng-Keng Chuang,1,2 Hung-Cheng Kan,1,2 I-Hung Shao1,2 1Division of Urology, Department of Surgery, LinKou Chang Gung Memorial Hospital, Taoyuan, Taiwan; 2Graduate Institute of Clinical Medical Sciences, College of Medicine, Chang Gung University, Taoyuan, Taiwan; 3Clinical Informatics and Medical Statistics Research Center, College of Medicine, Chang Gung University, Taoyuan, Taiwan; 4Division of Allergy, Asthma, and Rheumatology, Department of Pediatrics, Chang Gung Memorial Hospital at Linkou, Taoyuan, Taiwan *These authors contributed equally to this work Introduction: Renal cell carcinoma (RCC) is one of the most lethal urological malignancies, and surgeries remain the mainstay for localized RCC. This study aimed to compare the selection of open surgery and minimally invasive kidney surgery for RCCs for the aspects of complication, medical costs, and patient preference. Materials and methods: We conducted a population-based case–control study by using the National Health Insurance Research Database of Taiwan, which included data from 23 million Taiwanese residents. Patients newly diagnosed with RCC during 2006–2012 were included. We compared the general characteristics, underlying disease, complications, hospital stay, postoperative analgesic dosage, and medical costs between open group and minimally invasive group. Results: A total of 3,172 patients who received radical nephrectomy (RN) or partial nephrectomy (PN) for RCC were included. The mean age was 61.1 years, with a male to female ratio of 1.88. In the minimally invasive groups, the mean hospital stay was significantly shorter than in open groups (12.4 days in open RN versus 10.3 days in minimally invasive RN, and 9.7 days in open PN versus 8.2 days in minimally invasive PN). There was no significant difference between the medical costs and the incidence of major bleeding complication between the open group and the minimally invasive group. Female patients and patients with higher monthly income were more likely to receive minimally invasive surgery. Conclusion: During past decades, open RN has gradually been replaced by minimally invasive surgeries and PN. Compared to open surgeries, minimally invasive surgeries could lead to less postoperative pain and faster recovery. Economic status of the patients potentially hinders them from receiving minimally invasive surgeries, which may cost more. Keywords: renal cell carcinoma, minimally invasive, open surgery, complication, NHIRD